Climate Sensitivity and Feedback of a New Coupled Model (K-ACE) to Idealized CO2 Forcing - Min-Ah Sun (Atmosphere, 2020)
Climate sensitivity and feedback processes are important for understanding Earth’s system response to increased CO2 concentration in the atmosphere. Many modelling groups that contribute to Coupled Model Intercomparison Project phase 6 (CMIP6) have reported a larger equilibrium climate sensitivity (ECS) with their models compared to CMIP5 models. This consistent result is also found in the Korea Meteorological Administration Advanced Community Earth System model (K-ACE). Idealized climate simulation is conducted as an entry card for CMIP6 to understand Earth’s system response in new coupled models and compared to CMIP5 models. The ECS in the K-ACE is 4.83 K, which is higher than the range (2.1–4.7 K) of CMIP5 models in sensitivity to CO2 change and higher bound (1.8–5.6 K) of CMIP6 models. The radiative feedback consists of clear-sky and cloud radiative feedback. Clear-sky feedback of K-ACE is similar to CMIP5 models whereas cloud feedback of K-ACE is more positive. The result is attributable for strong positive shortwave cloud radiative effect (CRE) feedback associated with reduced low-level cloud cover at mid latitude in both hemispheres. Despite the cancellations in strong negative long wave CRE feedback with the changes in high-level clouds in the tropics, shortwave CRE has a dominant effect in net CRE. Detailed understanding of cloud feedback and cloud properties needs further study.